The contribution of individual differences in statistical learning to reading and spelling performance in children with and without dyslexia. (25th February 2021) - van Witteloostuijn, Merel; Boersma, Paul; Wijnen, Frank; Rispens, Judith
Abstract : Using an individual differences approach in children with and without dyslexia, this study investigated the hypothesized relationship between statistical learning ability and literacy (reading and spelling) skills. We examined the clinical relevance of statistical learning (serial reaction time and visual statistical learning tasks) by controlling for potential confounds at the participant level (e.g., non‐verbal reasoning, attention and phonological skills including rapid automatized naming and phonological short‐term memory). A 100 Dutch‐speaking 8‐ to 11‐year‐old children with and without dyslexia participated (50 per group), see also van Witteloostuijn et al. (2019) for a study with the same participants. No evidence of a relationship between statistical learning and literacy skills is found above and beyond participant‐level variables. Suggestions from the literature that the link between statistical learning and literacy attainment, and therefore its clinical relevance, might be small and strongly influenced by methodological differences between studies are not contradicted by our findings.